FACTORS ASSOCIATED WITH THE BEHAVIOR OF PERSONAL PROTECTIVE EQUIPMENT (PPE) IN WORKERS AT HEIGHT AT THE SAVYAVASA LUXURY RESIDENCE PROJECT IN 2023 - Haliqatul Zadidah; Rusman Effendi; Dihartawan (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Working at height is an activity or activity carried out by workers at a workplace on the surface of land or water where there is a height difference and has the potential to fall which could cause the worker or other people in the workplace to experience injury or death. Work accidents involving heights resulted in the deaths of 2.78 million workers per year in 2018. This research aims to look at the relationship between the independent variables (age, education, knowledge, attitudes, availability of PPE) and the dependent variable (the behavior of using PPE among workers in height). PT TAISEI-CSC JO Savyavasa Luxury Apartment Project. Samples were taken using a purposive sampling technique with a total of 120 respondents. Analysis was carried out bivariate using the chi-square test. A total of 77 (64.2) workers behaved badly. The results showed that there was a relationship between education (p=0.000), knowledge (0.000), and age (0.016). Suggestions for workers to further increase discipline in complying with applicable regulations. For the company to further improve K3 socialization.